The Role of Constitutional Courts in Promoting Healthcare Equity: Lessons from Hungary - Mária Éva Földes (The Constitutional Court of the Republic of Indonesia, 2020)
This paper explores whether constitutional litigation contributes to sustaining the equity element of the right to health. Equity entails a fair distribution of the burden of healthcare financing across the different socio-economic groups of the population. A shift towards uncontrolled private healthcare provision and financing raises equity challenges by disproportionately benefitting those who are able to afford such services. The extent to which equity is enforced is an indicator of the strength of the right to health. However, do domestic constitutional courts second-guess, based on equity, policy decisions that impact on healthcare financing? Is it the task of constitutional courts to scrutinize such policy decisions? Under what conditions are courts more likely to do so? The paper addresses these questions by focusing on the case of Hungary, where the right to health has been present in the Fundamental Law adopted in 2010 and the Constitutions preceding it. While the Hungarian Constitutional Court has been traditionally cautious to review policy decisions pertaining to healthcare financing, the system has been struggling with equity issues and successive government coalitions have had limited success in tackling these. The paper discusses the role of constitutional litigation in addressing such equity concerns. In doing so, it contributes to the discussion on the role of domestic constitutional courts in the protection of social and economic rights.